Relationship between Dividend Policy and Share Price - NTUI, Ponsian Prot; Yuda, Thadeo Yuda; Prosper, Kawiche Prosper; Samwel, Godfrey Samwel (Archives of Business Research, 2015)
The study aims to examine the relationship between dividend policy and share price in Dar Es Salaam Stock Exchange (DSE). The investigation is based on the listed companies for the period of five years from 17 companies on DSE where the data is extracted from the company’s annual reports in order to determine the relationship between dividend policy and share price. This is measured by dividend policy operationalized by four variables including D. yield, dividend payout ratio, E.vol and P/E ratio. The study is quantitative in nature where the SPSS is applied as tool of analysis by using descriptive, regression and correlation method for measure relationship. The results show that the best dividend policy is P/E ratio as indicated by the lowest P value and relationship between dividend policy and share price is that P/E ratio have positive relationship while other variables namely dividend yield, dividend payout ratio, earnings per share and price earnings ratio are negatively related.